Is It Justified To Use Arabic In English Class? Efficacy Of English-Arabic Bilingual Teaching For Teaching English At Elementary Level - Ahmed Benyo; Triyo Supriyatno; Anindita Borah; Tribhuwan Kumar (Ijaz Arabi Journal of Arabic Learning, 2022)
This study aims to determine the impact of integrating Arabic within teaching English as a Foreign Language in an elementary school environment in Saudi Arabia. Generally speaking, English language teachers strive to emphasize using the English language in their classes. They are confronted with a severe dilemma due to their efforts, namely a lack of communication between professors and students. These kids have difficulty comprehending what they perceive as a challenging foreign language.20 English teachers have been chosen as the participants in the study were chosen. The researcher employed a random sampling technique to select participants for the study. The researcher gathered information from participants using a questionnaire survey and a test administered by the researchers. Using Arabic as a facilitating aid in English classes in Saudi Arabia may positively or negatively impact teaching English as a foreign language, as per the findings of this study. The findings of this study necessitate future research to identify and examine the many sorts of relevant issues related to this study in a wide variety of fields.